OPTIMIZATION OF THE PROCESS OF ISOLATION OF AMINO ACID MIXTURES FROM L-PROLINE CULTURAL LIQUID (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The process of separation of biomass from L-proline cultural liquid has been investigated and the optimal technological parameters of the process has been defined. Proline sorption curves at various pH values of supernatant have been obtained and pH value, at which the maximum sorption of proline takes place on cationite as defined. The proline sorption isotherm from synthetic solution and supernatant of cultural liquid on the KU-$2× 8$ cation-exchange resin has been obtained and the coefficients of proline and accompanying amino-acids distribution has been calculated. The stationary front width of proline-ion sorption in dependence of supernatant flow rate has been studied and the optimal parameter of the process has been defined. On the basis of the data obtained, the proline sorption from cultural liquid supernatant in the industrial conditions on 4 m3 column has been carried out and proline sorption and accompanying admixture curves on KU-$2× 8$ cation-exchange resin have been obtained. The data obtained have been used as basis technology for working out of the amino acid mixtures from the cultural liquid of proline.